Factors associated with self-management in older adults with multiple chronic conditions: a qualitative study - Sadeghi, Hajar; Mohammadi Shahbolaghi, Farahnaz; Hosseini, Mohammadali; Fallahi-Khoshknab, Masoud; Ghaedamini Harouni, Gholamreza (Frontiers in Public Health, 2024)
Background and purpose Recognizing the importance of self-management in older adults with multiple chronic conditions (MCCs) is crucial for their quality of life. This qualitative study explored the factors linked to self-management among older adults with MCCs. Materials and methods The present study was conducted in three stages: an integrated review, qualitative interviews, and Delphi. The search used electronic databases including Web of Science, PubMed, Scopus, Magiran, SID, and Iranmedex. The results of 33 studies that met the inclusion criteria were analyzed using conventional content analysis. A data matrix was formed; and purposeful sampling was conducted among older adults with MCCs, family caregivers, and specialists. The data were collected through semi-structured interviews. Data analysis of 29 interviews was conducted simultaneously with data collection using oriented qualitative content analysis and the Elo and Kyngäs approach. Three rounds of Delphi were conducted via email correspondence with a group of 30 experts to develop and validate the proposed variables. Results The factors that influence self-management can be categorized into various categories. Biological factors, cognitive factors, co-morbidities, socio-economic factors, health-related behaviors, mental health, interactions with healthcare teams, Family relationships, medical facility resources, employee empowerment, health policy development, and cultural influences. Conclusion Self-management in older Iranian adults with MCCs is a complex and multidimensional phenomenon. By identifying the relevant factors, it is possible to design operational plans that promote self-management among the older adult population and are tailored to fit the specific needs of Iranian society.